Análisis de la Planta Turística oferta ocio y recreación del cantón Salcedo - Vega Bravo, Tania Maribel (2019)
The main objective of the research project is the analysis of the tourism, leisure and recreation facilities of Salcedo canton, which helped determine the existing places, in order to have a current record of the places that provide tourist services. In the execution of the present project, a situational diagnosis of the canton of Salcedo was carried out, through the collection of necessary information in secondary sources such as the Ministry of Tourism and the National Institute of Statistics and Census, the most important sources being the same as the data sources. Demographic, social and cultural such as population, ethnicity, festive traditions, natural and cultural attractions, gastronomy and economic activities in which each parish of the Salcedo canton is dedicated. An inventory of the places that provide leisure and recreational tourism services was developed through the design of the technical sheets based on the tourist establishments which are examined according to PLANDETUR 2016-2020 for the recognition of existing places in the Salcedo canton. , the same that are in function of the existing parishes in which aspects like general data were considered, the category of each establishment, the service that renders and the number of visits that they have weekly and annually. Through the investigation, information was collected by means of an on-site visit to each tourist establishment in which 33 places that provide tourist services were found, which were divided into recreation, night and religious establishments. A design of the leisure and recreation catalog was made through a digital diagramming software in which the main characteristics of the establishments are described, with 22 pages. The present project recommends to follow up the research for the updating of information since over time they can implement or reduce the leisure and recreation sites.